2012
DOI: 10.1152/ajpendo.00198.2012
|View full text |Cite
|
Sign up to set email alerts
|

Leucine supplementation increases SIRT1 expression and prevents mitochondrial dysfunction and metabolic disorders in high-fat diet-induced obese mice

Abstract: Li H, Xu M, Lee J, He C, Xie Z. Leucine supplementation increases SIRT1 expression and prevents mitochondrial dysfunction and metabolic disorders in high-fat diet-induced obese mice. Am J Physiol Endocrinol Metab 303: E1234 -E1244, 2012. First published September 11, 2012; doi:10.1152/ajpendo.00198.2012.-Leucine supplementation has been shown to prevent high-fat diet (HFD)-induced obesity, hyperglycemia, and dyslipidemia in animal models, but the underlying mechanisms are not fully understood. Recent studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 49 publications
5
110
2
5
Order By: Relevance
“…Proteins were extracted from cultured cells and mouse livers as described previously (19,33,54). The lysates were resolved by sodium dodecyl sulfate polyacrylamide gel electrophoresis, transferred to nitrocellulose membranes, and incubated with the appropriate specific antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were extracted from cultured cells and mouse livers as described previously (19,33,54). The lysates were resolved by sodium dodecyl sulfate polyacrylamide gel electrophoresis, transferred to nitrocellulose membranes, and incubated with the appropriate specific antibody.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the alteration of insulin signaling, the mice were injected intraperitoneally with insulin (0.15 U/g) or normal saline and euthanized 15 min later. Their livers were collected for Western blotting of phosphorylated Akt (33).…”
mentioning
confidence: 99%
“…Previous studies have reported that branched-chain amino acid (BCAA: valine, leucine, isoleucine) supplementation enhanced mitochondrial biogenesis in middle-aged mice 4) . Furthermore, leucine supplementation prevented high fat diet-induced metabolic disorders by enhancing mitochondrial biogenesis 5) . Moreover, glutamine is involved in leucine incorporation into the cell [6][7] .…”
Section: Introductionmentioning
confidence: 98%
“…Embora a associação da suplementação com restrição calórica seja pouco estudada, trabalhos tem demonstrado que a leucina, bem como seus metabólitos, pode aumentar a expressão da SIRT-1, demonstrando um papel em comum entre essas duas intervenções (BRUCKBAUER; ZEMEL, 2011;PETZ;KLAUS, 2014). Considerando essa relação, Li H, et al (2012), ofertaram 1,5g de leucina/100 ml a camundongos obesos e verificaram que a leucina apresentou correlação com o aumento da expressão da SIRT-1, com a melhora da sensibilidade à insulina e a redução do estresse oxidativo nos animais alimentados com dieta hiperlipídica. Além disso, o ganho de peso observado nos animais que receberam a suplementação não foi associado ao acúmulo de gordura ectópica no fígado e nos músculos.…”
Section: Leucina E Seus Efeitos No Fígadounclassified
“…Eles também podem atuar na regulação do peso corporal, na homeostase glicêmica e estimular a oxidação de ácidos graxos (GARCIA-CARABALLO et al, 2013;KAINULAINEN;HULMI e KUJALA, 2013;LYNCH;ADAMS, 2014). Dentre os BCAA, a suplementação isolada com leucina tem demonstrado resultados no que condiz com a perda de peso, melhora da sensibilidade à insulina e do perfil lipídico ZEMEL, 2011;LI et al, 2012), por atuar na regulação do metabolismo e equilíbrio energético, afetando diretamente os tecidos periféricos, tais como o tecido adiposo branco (TAB), músculos e fígado. No entanto, o efeito direto da leucina na sinalização hepática e os mecanismos associados ainda não são totalmente compreendidos (BINDER et al, 2013;LU et al, 2013;PÁDUA et al, 2009;PEDROSA et al, 2010).…”
Section: Introductionunclassified